‘We shift the channel when Mahathir appears’: the political internet and censorship in Malaysia. - Fischer, Johan (Universiti Kebangsaan Malaysia, 2009)
A powerful form of ethnic state nationalism, driven by the dominant political party in Malaysia United Malays National Organisation (UMNO), aspires to partake in globalisation by marketing information and communications technology (ICT), and the Internet in particular. The Internet has effected drastic political and cultural changes in contemporary Malaysia. This article argues that ‘the political’ in modern Malaysia is best explored in the interfaces between the state’s Internet fascination, censorship and authoritarianism on the one hand and, on the other hand, everyday media consumption in what Michael Herzfeld has called ‘cultural intimacy’ among the emerging Malay middle class. Discussing ethnographic material from suburban Malay middle-class homes collected in 2001-2002, I show how these Malays understand and appropriate the Islamic political party Parti Islam SeMalaysia’s (PAS) bid to promote itself as a modern and democratic party by launching the website HarakahDaily.net in the tense political and religious atmosphere post-9/11. I situate this piece of historical ethnography in recent transformations of the political Internet and censorship in Malaysia.